Chronic urticaria due to milk - Gupta, Ramji (Journal of Pakistan Association of Dermatologists, 2020)
A patient of urticaria due to milk and milk product is being reported. She was having urticaria since 8 months. The urticaria improves with antihistamine only. She was off the urticaria when she was put on total fast for 48 hour. Provocation test after 10th day with milk, she developed urticaria 8 hours after taking milk.